Effects of neem oil, Azadirachta indica A. juss on growth and survival of bagworm, Metisa plana (LEPIDOPTERA: PSYCHIDAE) LARVAE - Siti Nurulhidayah Ahmad,; Noorhazwani Kamarudin,; Saharul Abillah Mohamad,; Mohamad Rosman Sulaiman,; Muhammad Nurul Yaqin Syarif,; Mohamed Mazmira Mohd Masri,; Norhayu Asib, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Bagworm, Metisa plana Walker (Lepidoptera: Psychidae) is a major leaf-defoliating insect pest that has gained national attention due to the severe damage and loss to oil palm crops, notably in Peninsular Malaysia. The plant-derived insecticide neem, Azadirachta indica A. Juss provides a sustainable alternative as a biological control tool. This study was aimed to evaluate the growth and survival of M. plana after exposed to different concentrations of neem oil (75, 37.50, 18.75, 9.38, 4.69, and 2.35 mg/L) under laboratory conditions with distilled water used as control treatment. The bioassays of the neem extract were assessed using a leaf-dipping technique on fourth and fifth instar larvae stages of M. plana collected from Tapah, Perak, Malaysia. Observations were made during three exposure intervals: 1, 2, and 3 days after treatment (DAT). Higher concentrations of the neem oil had significantly increased the bagworm larval mortality at 3 DAT (ranging from 30% to 97.67%) and inhibited larvae growth which survived to adulthood. The highest % mortality was 96.67% and 83% for the fourth and fifth instar larvae after 3 DAT at a concentration of 75 mg/L, respectively. The lethal concentration, LC50 within 3 DAT indicated a value of 3.59 and 6.15 mg/L for the fourth and fifth instar larvae, respectively. The findings demonstrated that neem oil as an insect growth regulator exhibited inhibitory properties against the growth and survival of the bagworm larvae, resulting in a notable increase in mortality. Therefore, neem possesses the potential to be utilized as a substitute biopesticide for M. plana, which requires more field investigations.